Age and sex effects on paired-pulse suppression and prepulse inhibition of auditory evoked potentials - Inui, Koji; Takeuchi, Nobuyuki; Borgil, Bayasgalan; Shingaki, Megumi; Sugiyama, Shunsuke; Taniguchi, Tomoya; Nishihara, Makoto; Watanabe, Takayasu; Suzuki, Dai; Motomura, Eishi; Kida, Tetsuo (Frontiers in Neuroscience, 2024)
Responses to a sensory stimulus are inhibited by a preceding stimulus; if the two stimuli are identical, paired-pulse suppression (PPS) occurs; if the preceding stimulus is too weak to reliably elicit the target response, prepulse inhibition (PPI) occurs. PPS and PPI represent excitability changes in neural circuits induced by the first stimulus, but involve different mechanisms and are impaired in different diseases, e.g., impaired PPS in schizophrenia and Alzheimer’s disease and impaired PPI in schizophrenia and movement disorders. Therefore, these measures provide information on several inhibitory mechanisms that may have roles in clinical conditions. In the present study, PPS and PPI of the auditory change-related cortical response were examined to establish normative data on healthy subjects (35 females and 32 males, aged 19–70 years). We also investigated the effects of age and sex on PPS and PPI to clarify whether these variables need to be considered as biases. The test response was elicited by an abrupt increase in sound pressure in a continuous sound and was recorded by electroencephalography. In the PPS experiment, the two change stimuli to elicit the cortical response were a 15-dB increase from the background of 65 dB separated by 600 ms. In the PPI experiment, the prepulse and test stimuli were 2- and 10-dB increases, respectively, with an interval of 50 ms. The results obtained showed that sex exerted similar effects on the two measures, with females having stronger test responses and weaker inhibition. On the other hand, age exerted different effects: aging correlated with stronger test responses and weaker inhibition in the PPS experiment, but had no effects in the PPI experiment. The present results suggest age and sex biases in addition to normative data on PPS and PPI of auditory change-related potentials. PPS and PPI, as well as other similar paradigms, such as P50 gating, may have different and common mechanisms. Collectively, they may provide insights into the pathophysiologies of diseases with impaired inhibitory function.